(untitled) (Revista Contexto & Saúde, 2025)
The objective of this study was to map the existing evidence on the safety of nursing care in the preparation and administration of sedative, analgesic, and vasoactive drugs in critically ill patients. This scoping review involved searching the following databases: EMBASE, SCOPUS, PubMED/MEDLINE, Cochrane Library, CINAHL, and Web of Science. The search was supplemented with gray literature. Thirty-two studies were selected for review, with the majority (12) from the USA and one from Brazil. Of these, 16 were published in the last five years, and 18 focused on vasoactive care, while 11 dealt with analgesics and sedatives. The literature was reviewed to identify care for invasive/painful procedures and the role of nurses in this practice for sedatives and analgesics. Regarding vasoactive drugs, the following key points emerged: administration via peripheral routes, care with infusion pumps, communication, physicochemical incompatibilities, benefits of ready-to-use or premanipulated drugs, and implementation of care protocols. The publications describe the complexity and various precautions taken by the care team to ensure the safety of these medications.